The Law on Energy Performance of Buildings – a masterpiece of legislative or reject? - Panek, Małgorzata (Studia Iuridica Toruniensia, 2016)
The aim of this article is to evaluate the solutions for the practice of preparing the energy performance certificates of buildings, adopted in the Act of 3 March 2015 on the energy performance of buildings. The author first outlines the directions of the energy policy of the European Union’s energy security and environmental protection atmospheric, as well calls attention to the importance of enforcement of the order of EU countries, the obligation to prepare energy performance certificates for buildings. In the following part of the statement there are compiled EU regulations dealing with the obligation to prepare energy certificates and national regulations implementing them. The author assesses the degree of achievement of the European Union’s energy objectives, critically referring to inconsistencies and doubts resulting from the Act on Energy Performance of Buildings. On the basis of considerations they are formulated observations on the amendment to the Act on the need to increase the country’s energy efficiency and legal certainty.